2019
DOI: 10.1094/pdis-08-18-1333-re
|View full text |Cite
|
Sign up to set email alerts
|

AtoxigenicAspergillus flavusIsolates Endemic to Almond, Fig, and Pistachio Orchards in California with Potential to Reduce Aflatoxin Contamination in these Crops

Abstract: In California, aflatoxin contamination of almond, fig, and pistachio has become a serious problem in recent years due to long periods of drought and probably other climatic changes. The atoxigenic biocontrol product Aspergillus flavus AF36 has been registered for use to limit aflatoxin contamination of pistachio since 2012 and for use in almond and fig since 2017. New biocontrol technologies employ multiple atoxigenic genotypes because those provide greater benefits than using a single genotype. Almond, fig, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…The four types of aflatoxins are associated with a myriad of health threats including stunting, impaired food conversion, immunosuppression, liver The magnitude of the aflatoxin contamination problem differs between developed and developing nations. Regulations and strict limits (tolerance levels) are enforced in developed nations to protect consumers from contaminated foods and feeds [12][13][14][15]. In contrast, regulations in emerging and developing nations, if they exist, are poorly enforced with few exceptions.…”
Section: The Aflatoxin Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…The four types of aflatoxins are associated with a myriad of health threats including stunting, impaired food conversion, immunosuppression, liver The magnitude of the aflatoxin contamination problem differs between developed and developing nations. Regulations and strict limits (tolerance levels) are enforced in developed nations to protect consumers from contaminated foods and feeds [12][13][14][15]. In contrast, regulations in emerging and developing nations, if they exist, are poorly enforced with few exceptions.…”
Section: The Aflatoxin Problemmentioning
confidence: 99%
“…During a 10-year research effort, it was found both that VCG YV36, to which AF36 belongs, was the atoxigenic VCG most commonly encountered in California and that AF36 was successful in limiting aflatoxin content in commercially produced pistachio. Therefore, USEPA granted registration of AF36 for use in pistachio grown in California and Arizona (2012), and eventually (2017) in almond and fig in California [15,51]. The biocontrol product AF36 is now used in several states across the US, which makes it the most widely used aflatoxin biocontrol product in the world.…”
Section: From Single To Multiple Isolatesmentioning
confidence: 99%
See 3 more Smart Citations